Meatal Stenosis and Stricture Urethrae In Postoperative Patients of Urethroplasty: A Prospective Study - Sajid, Md Minhajuddin; Bhuiyan, Md Akbar Husain; Farooq, Md Abdullah Al; Rahman, MA Mushfiqur; Chowdhury, Tanvir Kabir; Habib, Md Golam; Walid, Adnan (Journal of Chittagong Medical College Teachers’ Association, 2017)
Background: The postoperative complications of urethroplasty in hypospadias surgery still remain a great challenge to Paediatric urologists. The aim of the study was to find out the cause and incidence of meatal stenosis and stricture urethra following urethroplasty and to solve the postoperative complication. Materials and methods : This Prospective study was carried out in the department of Paediatric Surgery, Chittagong Medical College Hospital from April 2013 to October 2014 for a total of 19 months. A total of 50 hypospadias patients were selected for this study. After urethroplasty, outcome was assessed in terms of meatal stenosis and stricture urethra in the study period. Results : Meatal stenosis occurred in 5 patients in first follow up, which responded to regular dilatation in 3 patients in second follow up and till the end of third follow up, 2 patients were continuing regular meatal dilatation. In this study, urethral stricture occurred in 2 patient (4%) in second follow up, which was treated with regular urethral dilatation under general anaesthesia. Conclusion : It is evident from this study that, meatal stenosis is not very uncommon after urethroplasty which can very easily be treated by regular meatal dilatation. Urethral stricture, though not common, can also be treated by regular urethral dilatation under General Anaesthesia (GA). JCMCTA 2017 ; 28 (1) : 13 - 16